PENERAPAN OUTBOUND KIDS DALAM MENINGKATKAN MOTORIK KASAR ANAK - Farhatin Masruroh; Muslimin Muslimin; Mutma’innah Sofyani (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2021)
Gross motor is a body movement that uses large muscles, either most or all of the limbs that are influenced by the maturity of the child itself. The formulation of the problem in this study is how the process of exercising for children's gross motor skills through the application of outbound kids games in improving physical motor skills and how the results of implementing outbound kids games in improving children's physical motoric in group B at RA Riyadul Ulum Botolinggo Bondowoso. The type of research used is Classroom Action Research (CAR) by solving learning problems in class, problem solving is done in a cycle. Each cycle consists of planning, action, observation, and reflection with the aim of improving the quality of learning in the classroom. Based on observational research, it can be seen that (1) the implementation of outbound kids to improve gross motor development of children at RA Riyadul Ulum includes; the teacher explains how to play outbound footprint and hand with the illustrated carpet media, one by one they walk, jump, on the footprint and hand media through illustrated commands made from the carpet, then the teacher asks again their movements, correct or not the sequence of movements according to the instructions from the picture . (2) The results showed an increase in aspects of children's gross motor development through outbound kids, namely pre-cycle, the percentage value reached 30%. The average achievement of the indicators for children is 3 after the Cycle I action is carried out, the percentage value reaches 50%. Meanwhile, the average achievement of the indicators achieved by children is 5. Actions in Cycle II, the percentage value reaches 100%. The average value of the child's indicator achievement is 7.8 which found a comparison on the level of gross motor development of children that children experienced an increase in gross motor development after outbound kids.